Hadith #2207 - Sunan Abi Dawud - Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Rukanah bin Yazid from the Prophet (ﷺ) through a different chain of narrators.
Grade: Hasan

Hadith #2242 - Sunan Abi Dawud - al-Dhak bin Fyrwz al-Dylmy الضحاك بن فيروز الديلمي; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Yahya bin Ma'in يحيى بن معين; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Qais bin Al Harith through a different chain of narrators to the same effect.
Grade: Sahih

Hadith #2582 - Sunan Abi Dawud - Anas ibn Malik; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
Qatadah said “Taking another horse behind one’s horse to urge it on and taking another horse at one’s side are (done) in a horse race.
Grade: Sahih

Hadith #2610 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
‘Abd Allaah bin ‘Umar said “The Apostle of Allaah(ﷺ) prohibited to travel with a copy of the Qur’an to the enemy territory. The narrator Malik said “(It is) I think lest the enemy should take it.
Grade: Sahih

Hadith #2645 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; ibn Abbas; Ikrama عكرمة; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent an expedition to Khath’am. Some people sought protection by having recourse to prostration, and were hastily killed. When the Prophet (ﷺ) heard that, he ordered half the blood-wit to be paid for them, saying: I am not responsible for any Muslim who stays among polytheists. They asked: Why, Messenger of Allah? He said: Their fires should not be visible to one another. Abu Dawud said: Hushaim, Ma’mar, Khalid b. al-Wasiti and a group of narrators have also na
Grade: Sahih

Hadith #2702 - Sunan Abi Dawud - Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Sulaiman bin Harb سليمان بن حرب; Y'la bin Hkym al-Thqfy يعلى بن حكيم الثقفي (Sunan Abi Dawud)
‘Abd Allaah bin Mughaffal said “On the day of Khaibar a skin of fat was hanging. I came to it and clung to it. I then said (i.e., thought) I shall not give any one any of it today. I then turned round and saw the Apostle of Allaah(ﷺ) smiling at me.
Grade: Sahih

Hadith #3074 - Sunan Abi Dawud - Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone brings barren land into cultivation, it belong to him. He then transmitted a similar tradition mentioned above (No. 3067). He (‘Urwah) said: One who transmitted this tradition to me said that two persons brought their dispute to the Messenger of Allah (ﷺ). One of them grew palm trees in the land of the other. He decided to return the land to its owner of the palm-trees to remove his palm-trees. He said: I saw when their roots were being struck with axes. The
Grade: Hasan

Hadith #3087 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Ibn Ishaq محمد بن إسحاق بن يسار‎; Isma'il bin Umayya bin 'Amr إسماعيل بن أمية بن عمرو; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
Al-Miqdad went to Baqi’ al-Khabkhabah for a certain need. He found a mouse taking out a dinar from a hole. It then continued to take out dinars one by one until it took out seventeen dinars. It then took out a red purse containing a dinar. There were thus eighteen dinars. He took them to the Prophet (ﷺ), informed him and said to him: Take its sadaqah. The Prophet (ﷺ) asked him: Did you extend your hand toward the hole? He replied: No. The Messenger of Allah (ﷺ) then said: May Allah bless
Grade: Da'if

Hadith #3753 - Sunan Abi Dawud - Harun bin Zayd bin Abi al-Zarqa' هارون بن زيد بن أبي الزرقاء التغلبي; ibn Abbas; Ikrama عكرمة; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد (Sunan Abi Dawud)
When the verse: “O ye who believe! eat not up your property among yourselves in vanities, but let there be amongst you traffic and trade by mutual good will” was revealed, a man thought it a sin to eat in the house of another man after the revelation of this verse. Then this (injunction) was revealed by the verse in Surat an-Nur: “No blame on you whether you eat in company or separately.” When a rich man (after revelation) invited a man from his people to eat food in his house, he would
Grade: Hasan

Hadith #3800 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Muhammad bin 'Abdullah Abu محمد بن عبد الله أبو عبيد (Sunan Abi Dawud)
The people of pre-Islamic times used to eat some things and leave others alone, considering them unclean. Then Allah sent His Prophet (ﷺ) and sent down His Book, marking some things lawful and others unlawful; so what He made lawful is lawful, what he made unlawful is unlawful, and what he said nothing about is allowable. And he recited: “Say: I find not in the message received by me by inspiration any (meat) forbidden to be eaten by one who wishes to eat it….” up to the end of the verse
Grade: Sahih

Hadith #3859 - Sunan Abi Dawud - Anas ibn Malik; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to have himself cupped on the top of his head and between his shoulders, and that he used to say: If anyone pours out any of his blood, he will not suffer if he applies no medical treatment for anything.
Grade: Sahih

Hadith #3938 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
If anyone emancipates his share in a slave, he is to be completely emancipated by his money if he has money. But if he has no money, a fair price for the slave should be fixed, and the slave is required to work for his master according to the proportion of his price, but he must not be overburdened. Abu Dawud said: In the version of both the narrators the words are “he will be required to work and must not be overburdened”. This is the version of ‘Ali.
Grade: Sahih

Hadith #4191 - Sunan Abi Dawud - Abdullah ibn Ja'far; al-Hasan bin Sa'd bin Ma'bad الحسن بن سعد بن معبد; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Uqba bin Mukaram bin Aflah al-''Ami عقبة بن مكرم; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد (Sunan Abi Dawud)
The Prophet (ﷺ) came to Mecca and he had four plaits of hair.
Grade: Sahih

Hadith #4249 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; ibn Umar; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: Woe to Arabs because of evil which has drawn near! He will escape who restrains his hand.
Grade: Sahih

Hadith #4297 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; ibn Umar; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
The Prophet (ﷺ) said: The people will soon summon one another to attack you as people when eating invite others to share their dish. Someone asked: Will that be because of our small numbers at that time? He replied: No, you will be numerous at that time: but you will be scum and rubbish like that carried down by a torrent, and Allah will take fear of you from the breasts of your enemy and last enervation into your hearts. Someone asked: What is wahn (enervation). Messenger of Allah (ﷺ): He
Grade: Sahih

Hadith #4399 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Zbyan al-Quraishi أبو ظبيان القرشي; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; ibn Abbas; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد (Sunan Abi Dawud)
Ibn Abbas said: A lunatic woman who had committed adultery was brought to Umar. He consulted the people and ordered that she should be stoned. Ali ibn AbuTalib passed by and said: What is the matter with this (woman)? They said: This is a lunatic woman belonging to a certain family. She has committed adultery. Umar has given orders that she should be stoned. He said: Take her back. He then came to him and said: Commander of the Faithful, do you not know that there are three people whose actions
Grade: Sahih

Hadith #4724 - Sunan Abi Dawud - Abdul A'ala bin Hamad bin Nasr al-Bahli عبد الأعلى بن حماد بن نصر الباهلي النرسي; Ahmed bin Sa'id bin Ibrahim أحمد بن سعيد بن إبراهيم الرباطي; Ibn Ishaq محمد بن إسحاق بن يسار‎; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Jbyr bin Muhammad bin Jbyr جبير بن محمد بن جبير; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Bashar Bindar محمد بن بشار بندار; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Y'aqub bin 'Utba bin al-Mughira يعقوب بن عتبة بن المغيرة بن الأخنس (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Simak through a different chain of narrators to the same effect.
Grade: Da'if

Hadith #4815 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Ishaq bin Suwayd bin Hubayra إسحاق بن سويد بن هبيرة; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Umar ibn al-Khattab (Sunan Abi Dawud)
Avoid sitting in the roads. The people said: Apostle of Allah! We must have meeting places in which to converse. The apostle of Allah (ﷺ) said: If you insist on meeting, give the road its due. They asked: What is the due of roads, Apostle of Allah? He replied: Lowering the eyes, removing anything offensive, returning salutation, commanding what is reputable and forbidding what is disreputable.
Grade: Sahih

Hadith #5121 - Sunan Abi Dawud - Da'ud bin al-Husain al-Amwy داود بن الحصين الأموي; Ibn Ishaq محمد بن إسحاق بن يسار‎; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Muhammad bin 'Abdul Rahim bin Abi Zuhayr محمد بن عبد الرحيم بن أبي زهير البزاز (Sunan Abi Dawud)
he who summons others to party-spirit does not belong to us; and he who dies upholding party spirit does not belong to us.’
Grade: Da'if